Deconstruction of the Misconception of Kafā'ah: Reinterpretation Based on Comparative Analysis of Madhhab - Nisaul Qoimah (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2025)
The concept of kafa'ah in Islamic marriage is often misunderstood as a form of rigid social classification or even considered a requirement for a valid marriage. In fact, kafa'ah in classical fiqh literature is intended to create harmony in the household through the compatibility of spouses in religious, moral, and social aspects. However, there are significant differences in the understanding of kafa'ah among the imams of the madhhabs ranging from the criteria set, the level of urgency, to its implications for the validity of marriage. These differences in interpretation have caused confusion among contemporary Muslim communities and require in-depth comparative studies to correct the misconceptions that have developed. The research is centered on Islamic marriage practices and legal thought and seeks to clarify how kafa’ah can be applied more inclusively and justly in the context of modern society. The findings suggest that kafa’ah should not be reduced to rigid standards but seen as a flexible principle rooted in justice and mutual respect, capable of adapting to contemporary realities to ensure sustainable and harmonious marriages.